Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/ped.13990
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric profile of the Ages and Stages Questionnaires, Japanese translation

Abstract: BackgroundThis study assessed the psychometric profile of 10 questionnaires (every 6 months, from 6 to 60 months) from the Japanese translation of the Ages and Stages Questionnaires, third edition (J‐ASQ‐3).MethodsData from 439 children in a birth cohort were used to identify the J‐ASQ‐3 score distribution, establish cut‐off scores, and calculate the instrument's internal consistency. Data were also collected from 491 outpatients to examine J‐ASQ‐3 test–retest reliability and concurrent validity, which was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 17 publications
2
110
0
Order By: Relevance
“…The mean scores were also lower compared to the original scores from the ASQ manual. As it was discussed in the recent literature from Japan, for the questionnaires for younger children, the scores tended to be lower for the J-ASQ-3 [21]. This is consistent with other developmental assessment tools that showed that Japanese children generally develop slower than American children until about two years of age [22].…”
Section: Discussionsupporting
confidence: 86%
“…The mean scores were also lower compared to the original scores from the ASQ manual. As it was discussed in the recent literature from Japan, for the questionnaires for younger children, the scores tended to be lower for the J-ASQ-3 [21]. This is consistent with other developmental assessment tools that showed that Japanese children generally develop slower than American children until about two years of age [22].…”
Section: Discussionsupporting
confidence: 86%
“…Besides, we also conducted the analyses excluded infants with congenital heart diseases, because infants who had such diseases are known to be at high risk for developmental delay [21]. Furthermore, we conducted the analyses using the cutoff score of each J-ASQ-3 domain reported for Japanese children [19]. Information regarding paternal age at registration, presence of siblings, parents' educational level, and household income was collected from the parents' self-administered questionnaires.…”
Section: Resultsmentioning
confidence: 99%
“…The response options “yes,” “sometimes,” or “not yet,” scored 10, 5, and 0, respectively, and the total points for each domain are calculated. For each domain, a cutoff score is determined by subtracting two standard deviations from the mean for each applied month; if the score is less than the cutoff, the child is evaluated as “requiring a referral for further assessment.” We used the Japanese translation of the ASQ-3 (J-ASQ-3) [ 19 ] for the evaluation of developmental outcomes at age 1 year, but the cutoff score was taken from the original ASQ-3 because its psychometric profile has been validated. The details of the ASQ-3 were provided by Squires and Bricker [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…These subcomponents' scores and total score were calculated, and the correlation between these scores and MIBS‐J scores were evaluated. Reliability and validity as well as usefulness as a screening tool of this scale in Japanese population have been confirmed …”
Section: Methodsmentioning
confidence: 71%
“…Reliability and validity as well as usefulness as a screening tool of this scale in Japanese population have been confirmed. 23…”
Section: Assessment Of Infant Mental and Physical Developmentmentioning
confidence: 99%